Efficacy and safety of antiviral treatments for symptomatic COVID-19 outpatients: network meta-analysis and budget impact analysis - Berti, Giacomo; Mengato, Daniele; Ocagli, Honoria; Chinellato, Gianmarco; Mazzitelli, Maria; Cattelan, Anna Maria; Baldi, Ileana; Venturini, Francesca (Frontiers in Pharmacology, 2025)
IntroductionRemdesivir (RDV) and nirmatrelvir/ritonavir (NRM/RTV) are two antiviral agents for treating outpatient adults with mild to moderate symptomatic COVID-19 at high risk of developing a severe disease. The review objectives are to compare the efficacy and safety of these antivirals based on published RCT and real-world data, and to evaluate costs from a healthcare perspective.MethodsThis study provides a network meta-analysis of RDV and NRM/RTV for early treatment of COVID-19. The outcomes analysed were hospitalisation for any cause and serious adverse events. A cost-analysis was performed incorporating drug costs, administration, hospitalisations, and management of adverse events. A budget impact analysis was estimated for the University Hospital of Padua.ResultsOur results indicated that RDV showed a trend towards a lower risk of hospitalisation compared to NRM/RTV (RR 1.59, 95% CI: 0.60–4.20), though this was not statistically significant. For safety, NRM/RTV demonstrated a slightly lower risk of serious adverse events compared to RDV (RR 0.92, 95% CI: 0.31–2.74), but without statistical significance. A cost analysis showed that NRM/RTV could save €550,854.46 per 1,000 patients. Finally, a budget impact analysis based on data from the University Hospital of Padua estimated annual savings of €210,977.25 if all early treatments were administered with NRM/RTV instead of RDV.DiscussionThe comparison of the two antiviral therapies for the early treatment of COVID-19 did not yield statistically significant differences in the potential efficacy and safety to prevent hospitalisation or serious adverse events. However, the results of the cost-analysis showed a saving in favour of NRM/RTV.